2007
DOI: 10.4049/jimmunol.178.5.3244
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Mediates In Vivo IL-9 Activities on Lung Epithelial Cells but Not on Hematopoietic Cells

Abstract: Increased IL-9 expression, either systemically or under the control of lung-specific promoter, induces an asthma-like phenotype, including mucus overproduction, mastocytosis, lung eosinophilia, and airway hyperresponsiveness. These activities correlate with increased production of other Th2 cytokines such as IL-4, IL-5, and IL-13 in IL-9 Tg mice. To determine the exact role of IL-13 in this phenotype, mice overexpressing IL-9 were crossed with IL-13-deficient mice. In these animals, IL-9 could still induce mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 55 publications
(53 reference statements)
1
69
0
Order By: Relevance
“…IL-9R Ϫ/Ϫ mice were generated in the C57BL/6 background by deletion of the exons 2-6 of the IL-9R␣-chain, corresponding to the extracellular part of the receptor as described in Ref. 5. For the current study, IL-9R Ϫ/Ϫ mice were backcrossed for five generations onto BALB/c background.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-9R Ϫ/Ϫ mice were generated in the C57BL/6 background by deletion of the exons 2-6 of the IL-9R␣-chain, corresponding to the extracellular part of the receptor as described in Ref. 5. For the current study, IL-9R Ϫ/Ϫ mice were backcrossed for five generations onto BALB/c background.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that Retnla was induced by IL-9 in an IL-13-dependent way in lungs (5). We therefore analyzed the colonic expression of Retnla in our model.…”
Section: Pla2g4c and Resistin-like ␣ But Not Paneth Cell Markers Armentioning
confidence: 99%
See 1 more Smart Citation
“…Asthmatic patients show increased expression of IL-9 and its receptor in the airways (19). Many of the effects of IL-9 in mice (eosinophilic inflammation and mucus hypersecretion) are mediated via the release of IL-13, whereas its effects on mast cell expansion and B cells seem to be direct (20). IL-9 plays an important role in differentiation and proliferation of mast cells and interacts synergistically with SCF.…”
Section: Figurementioning
confidence: 99%
“…Swiss mice were obtained from Janvier (Elevage Janvier, Le GenestSt-Isle, France). As previously described, 36 IL-9R KO mice were obtained in the C57BL6 background by replacing a 2.8-kb genomic KpnI-SpeI fragment containing exons 2-6 by a neomycin resistance gene, leading to a complete loss of the extracellular binding domain.…”
Section: Kdamentioning
confidence: 99%